1998
DOI: 10.1128/iai.66.6.2501-2508.1998
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Clostridium perfringens Epsilon-Toxin for the Rat Hippocampus via the Glutamatergic System

Abstract: The neurotoxicity of epsilon-toxin, one of the major lethal toxins produced by Clostridium perfringens type B, was studied by histological examination of the rat brain. When the toxin was injected intravenously at a lethal dose (100 ng/kg), neuronal damage was observed in many areas of the brain. Injection of the toxin at a sublethal dose (50 ng/kg) caused neuronal damage predominantly in the hippocampus: pyramidal cells in the hippocampus showed marked shrinkage and karyopyknosis, or so-called dark cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 40 publications
7
30
2
1
Order By: Relevance
“…First, it was found that ETX injected at a low dose in rats rapidly (4 h) induces neuronal damage, characterized by cell shrinking, vacuolation and nucleus pyknosis, mainly in the hippocampus and cortex. These effects were not accompanied by perivascular edema or a reduction in blood flow in the hippocampus and were specifically inhibited by glutamate receptor inhibitors, indicating that ETX interferes directly with glutamatergic neurons [70]. It was then shown that ETX increases glutamate release from mouse hippocampus and not from other brain areas [71].…”
Section: Etx Stimulates Glutamate Releasementioning
confidence: 99%
“…First, it was found that ETX injected at a low dose in rats rapidly (4 h) induces neuronal damage, characterized by cell shrinking, vacuolation and nucleus pyknosis, mainly in the hippocampus and cortex. These effects were not accompanied by perivascular edema or a reduction in blood flow in the hippocampus and were specifically inhibited by glutamate receptor inhibitors, indicating that ETX interferes directly with glutamatergic neurons [70]. It was then shown that ETX increases glutamate release from mouse hippocampus and not from other brain areas [71].…”
Section: Etx Stimulates Glutamate Releasementioning
confidence: 99%
“…Epsilon toxin is a major virulence determinant of Clostridium perfringens types B and D, which cause fetal enterotoxemia of domestic animals [1]. Neurologic features, such as tremor and opisthotonus, which are characteristically observed during the course of the enterotoxemia [2], can be induced by epsilon intoxication in experimental models [3,4]. The toxin accumulates mainly in the brain and a high-a¤nity binding site for epsilon toxin exists in the synaptosomal membrane [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the lethal activity of the toxin was reduced by dopamine receptor antagonists and by drugs which directly or indirectly inhibit dopamine release, indicating that the toxin specifically stimulates release of dopamine from dopaminergic nerve endings [57]. In another study, prior injection of either a presynaptic glutamate release inhibitor or a glutamate receptor antagonist protected the rat hippocampus from toxin-induced neuronal damage, indicating that the toxin specifically stimulates glutamate release [53]. Stimulated release of glutamate was also demonstrated in the mouse hippocampus after intravenous administration of the toxin, leading to seizure and neuronal damage [58].…”
Section: Evidence For Neurotoxicitymentioning
confidence: 95%